Analisis Minat Investasi Gen-Z Terhadap Investasi di Pasar Modal Syariah (Studi Pada Mahasiswa UIN Fatmawati Sukarno Bengkulu) - Yustati, Herlina; Harpepen, Andi (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2023)
The research aims to determine the effect of the independent variables on the dependent variable. The independent variables are Islamic Investment Gallery (GIS), Financial Literacy, Minimum Capital, Technology, Social Media, while the dependent is Interest. Total 50 samples from students of the Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, who were in the Z generation category. This type of quantitative research was used with a purposive sampling method. Multiple Linear Regression Analysis Techniques using the Statistical Product and Service Solution (SPSS) program. The results showed that the regression coefficient value of the Islamic Investment Gallery (X1) (0.023) <0.05, so that it has a positive and significant effect on investment interest. While the regression coefficient value of the Financial Literacy variable (X2) (0.199) > 0.05, so it has no positive and significant effect on investment interest. Likewise with the value of the regression coefficient for the Minimum Capital variable (X3); Technology (X4); and Social Media (X5) which has a sig value (0.075) > 0.05; (0.107) > 0.05; and (0.386) > 0.05. Meanwhile, simultaneously all the variables studied had a significant effect on Gen Z Investment Interest in the Faculty of Islamic Economics and Business, and had an effect of 81.5%. While the remaining 18.5% is influenced by variables not examined in this study.